Ultrasound: Basic understanding and learning the language - Ihnatsenka, Barys (Medknow Publications, 2010)
Ultrasound (US) use has rapidly entered the field of acute pain medicine and regional anesthesia and interventional pain medicine over the last decade, and it may even become the standard of practice. The advantages of US guidance over conventional techniques include the ability to both view the targeted structure and visualize, in real time, the distribution of the injected medication, and the capacity to control its distribution by readjusting the needle position, if needed. US guidance should plausibly improve the success rate of the procedures, their safety and speed. This article provides basic information on musculoskeletal US techniques, with an emphasis on the principles and practical aspects. We stress that for the best use of US, one should venture beyond the “pattern recognition” mode to the more advanced systematic approach and use US as a tool to visualize structures beyond the skin (sonoanatomy mode). We discuss the sonographic appearance of different tissues, introduce the reader to commonly used US-related terminology, cover basic machine “knobology” and fundamentals of US probe selection and manipulation. At the end, we discuss US-guided needle advancement. We only briefly touch on topics dealing with physics, artifacts, or sonopathology, which are available elsewhere in the medical literature.